Andragogy Training Model in Advanced Level Training by Early Childhood Educators to Improve Learning - Yuliani, Lulu; Hufad, Achmad; Komar, Oong; Karwati , Lilis; Hamdan, Ahmad (Journal of Nonformal Education, 2024)
level training is a curriculum designed to enhance the knowledge, abilities, and attitudes of early childhood educators throughout the material-deepening phase of their professional tasks. This teaching strategy targets adults, namely early childhood educators. This study's objective was an advanced description of the andragogy training paradigm. This study used a qualitative approach and descriptive methodologies. It utilized data-gathering methods, including observation, interviews, and documentation. The findings of this study indicated that the training was conducted in accordance with the andragogy philosophy. Training at the advanced level in managing the education and training process with an andragogy approach included: (1) planning learning designs; (2) implementing learning activities with methods and techniques appropriate for adult learning; (3) evaluating learning outcomes and diagnosing learning needs; (4) Creating an environment and climate that encourages individual learning; (5) Developing tools and strategies that facilitate collaborative learning; (6) Diagnosing unique learning requirements; and (7) Formulating training program objectives based on the needs of the learners. The andragogy training approach does an outstanding job of providing early childhood educators with advanced training and enhancing early childhood learning.